Global Consortium Study of Neurological Dysfunction in COVID-19 (GCS-NeuroCOVID): Study Design and Rationale - Frontera, Jennifer; Mainali, Shraddha; Fink, Ericka L.; Robertson, Courtney L.; Schober, Michelle; Ziai, Wendy; Menon, David; Kochanek, Patrick M.; Suarez, Jose I.; Helbok, Raimund; McNett, Molly; Chou, Sherry H.-Y. (Neurocritical care, 2020)
Background As the COVID-19 pandemic developed, reports of neurological dysfunctions spanning the central and peripheral nervous systems have emerged. The spectrum of acute neurological dysfunctions may implicate direct viral invasion, para-infectious complications, neurological manifestations of systemic diseases, or co-incident neurological dysfunction in the context of high SARS-CoV-2 prevalence. A rapid and pragmatic approach to understanding the prevalence, phenotypes, pathophysiology and prognostic implications of COVID-19 neurological syndromes is urgently needed. Methods The Global Consortium to Study Neurological dysfunction in COVID-19 (GCS-NeuroCOVID), endorsed by the Neurocritical Care Society (NCS), was rapidly established to address this need in a tiered approach. Tier-1 consists of focused, pragmatic, low-cost, observational common data element (CDE) collection, which can be launched immediately at many sites in the first phase of this pandemic and is designed for expedited ethical board review with waiver-of-consent. Tier 2 consists of prospective functional and cognitive outcomes assessments with more detailed clinical, laboratory and radiographic data collection that would require informed consent. Tier 3 overlays Tiers 1 and 2 with experimental molecular, electrophysiology, pathology and imaging studies with longitudinal outcomes assessment and would require centers with specific resources. A multicenter pediatrics core has developed and launched a parallel study focusing on patients ages <18 years. Study sites are eligible for participation if they provide clinical care to COVID-19 patients and are able to conduct patient-oriented research under approval of an internal or global ethics committee. Hospitalized pediatric and adult patients with SARS-CoV-2 and with acute neurological signs or symptoms are eligible to participate. The primary study outcome is the overall prevalence of neurological complications among hospitalized COVID-19 patients, which will be calculated by pooled estimates of each neurological finding divided by the average census of COVID-19 positive patients over the study period. Secondary outcomes include: in-hospital, 30 and 90-day morality, discharge modified Rankin score, ventilator-free survival, ventilator days, discharge disposition, and hospital length of stay. Results In a one-month period (3/27/20–4/27/20) the GCS-NeuroCOVID consortium was able to recruit 71 adult study sites, representing 17 countries and 5 continents and 34 pediatrics study sites. Conclusions This is one of the first large-scale global research collaboratives urgently assembled to evaluate acute neurological events in the context of a pandemic. The innovative and pragmatic tiered study approach has allowed for rapid recruitment and activation of numerous sites across the world—an approach essential to capture real-time critical neurological data to inform treatment strategies in this pandemic crisis.